Cross-infection control in clinical training: Development of a device for storing a composite resin in restorative dentistry - de Oliveira, Ana Luísa Botta Martins; Wajngarten, Danielle; Presoto, Cristina Dupim; de Oliveira Barud, Hélida Gomes; Domeneguetti, Rafael Romano; Botta, Ana Carolina; Garcia, Patricia Petromilli Nordi Sasso (Wiley, 2018)
This study presented a biosafety device for the hygienic storage of composite resin during restorative procedures in teaching clinics, RESTAURASAFE, and to compare the color stability, surface hardness, and degree of conversion of the composite resin made with the proposed device to those of conventionally made resins. Esthet-X HD composite was manipulated directly from the syringe, fractionated doses, dappen dish or RESTAURASAFE. Disc-shaped specimens were immersed in artificial saliva and coffee for 60 days and the color stability and the Vickers surface hardness were evaluated during 60 days. Degree of conversion was assessed after immersing specimens in saliva (baseline). The surface morphology analysis of composite resin has taken by scanning electron microscopy (SEM). The data were evaluated statistically by repeated measures ANOVA (α=.05). No difference of color stability was observed for saliva and coffee regardless of storing devices. The resin manipulated directly from the syringe presented lower hardness, and fractionated doses presented lower degree of conversion than the RESTAURASAFE. SEM analysis showed that after artificial aging in coffee for 60 days, the specimens prepared with fractionated doses of resin displayed the fewest changes in surface morphology, followed by those prepared with the RESTAURASAFE. We conclude that RESTAURASAFE allows to obtain similar color stability, higher hardness, and degree of conversion of the composite in comparison to the other storing devices.
Keywords: clinical training; composite resin restoration; cross-infection control; dental education